PERKEMBANGAN PERATURAN TENTANG ZAKAT DI INDONESIA - Widi Nopiardo (Institut Agama Islam Negeri Batusangkar, 2019)
Regulation on zakat is made by the Government with the aim of realizing good zakat governance. Along with the times, existing regulations sometimes no longer accommodate the problem of zakat management in the field. Therefore, the latest regulations are needed regarding the management of zakat. This type of research is library research (library research) using descriptive qualitative analysis. The results of the study show that from 1951 d.d. 2017 there are various regulations regarding zakat, starting from Ministerial Regulations, Presidential Regulations, Government Regulations to Laws. But unfortunately the Law on the management of new zakat was born at the age of independence of the Republic of Indonesia Unitary State which is quite old, namely 54 years. This is marked by the birth of Law No. 38 of 1999 concerning Management of Zakat. In its development Law No. 38 of 1999 was revised to achieve the optimization of zakat management in Indonesia. The result of the revision was the establishment of Law Number 23 of 2011 concerning Management of Zakat. Followed by the issuance of Government Regulation of the Republic of Indonesia Number 14 of 2014 concerning Implementation of Law Number 23 Year 2011 concerning Management of Zakat. In addition, the Presidential Instruction (Inpres) No. 3 of 2014 concerning Optimization of Zakat Collection in Ministries / Institutions, Secretariat General of State Institutions, Secretariat General of State Commissions, Regional Governments, State-Owned Enterprises and Regional-Owned Enterprises through the National Amil Zakat Agency.